The Impact of Blockchain Technology to the Efficiency and Profitability Bank in Indonesia - Agus Saur Utomo; Mahendra Galih Prasaja; Nayla Fahiya Rahmawati (LP2M IAIN Palopo, 2024)
ABSTRACT. This research empirically examines the impact of blockchain adoption to the bank’s profitability and efficiency in Indonesia. Descriptive statistic and paired sample t-test are employed to analyses the data. The sample of this study is Bank Permata, a pioneer bank in Indonesia that adopted blockchain technology. Bank Permata have a conventional service as well as syariah service unit. Secondary data was taken from bank’s financial report as long as 2019-2023. Efficiency is proxied by BOPO ratio while profitability is proxied by ROA, ROE, GPM, OPM and NPM ratios. The study found that blockchain technology doesn’t have significant impact to the bank efficiency, however the level of bank efficiency is increasing after implementing blockchain. Bank profitability is partly affected by adoption of blockchain technology. GPM, OPM and NPM are significantly different after implementing the blockchain however ROA and ROE are not significantly different. Nevertheless, there are increasing ROA and ROE ratio after blockchain adoption.